Synthesis and Cytotoxic Activity of N,N′-(Arylmethylene)bisamides - Uenishi, Junichi; Hirano, Hirokazu; Ueda, Tsuyoshi; Hoshiya, Naoyuki; Ii, Hiromi; Yoshiki, Tatsuhiro (Synthesis, 2015)
N,N′-(Arylmethylene)bisamides were prepared by an acid-catalyzed reaction of arylaldehydes with cinnamamide or acrylamides. The reaction was carried out in refluxing toluene for a few hours, and simple collection of the precipitate gave the desired products. The bisamides were designed as cytotoxic molecules based on the structure of the potently cytotoxic marine natural product (–)-zampanolide. The activities of the bisamides against two cancer cell lines were evaluated, and several compounds were found to show medium potency with IC50 values in the lower micromolar level.
Keywords: amides; medicinal chemistry; cytotoxins; condensation; bisamides